Sex Pheromones of the Potato Tuber Moth (Phthorimaea operculella) - Pan, Huanhuan; Zhao, Hongyi; Ai, Likun; Huang, Jian; Chen, Yang (Frontiers in Chemistry, 2022)
The potato tuber moth (Phthorimaea operculella) is a major potato pest. Its sex pheromones contain two chemical structures: 4E,7Z-tridecadiene-1-ol acetate (PTM1) and 4E,7Z,10Z-tridecatriene-1-ol acetate (PTM2). Increasing global consciousness of environmental protection is driving widespread attention to the possible use of these pheromones for sustainable pest management. This review summarizes research on the structure confirmation, field application, and chemical synthesis of the sex pheromones of the potato tuber moth. An efficient synthesis strategy of the two sex pheromones is proposed.